The role of global logistics companies in disaster relief efforts : an investigation into benefits, challenges and critical success factors of cross-sector collaborations : a thesis presented in partial fulfilment of the requirements for the degree of Master of Logistics and Supply Chain Management at Massey University, Albany, New Zealand - Maether, Jan (Massey University, 2010)
The purpose of this thesis is to explore the benefits and opportunities, as well as the challenges and risks cross-sector collaborations in humanitarian aid and disaster relief generate. The study also points out the major critical success factors that commercial logistics companies and humanitarian aid organisations require in order to build efficient partnerships. Additionally, guiding recommendations that support the development of successful collaborative efforts are presented. The study is based on an extensive literature review discussing the complexities of humanitarian aid logistics and reveals the differences between commercial and disaster relief supply chains. Different types of corporate-humanitarian collaborations and cross-learning potential are highlighted. The literature review also deals with the possibility of establishing partnerships within the framework of corporate social responsibility (CSR). A questionnaire investigates the respondents‟ point of view about the strengths, opportunities, and risks of cross-sector collaborations as well as requirements for successful partnerships. Case studies are also included in this thesis in order to discuss strengths and weaknesses and to pinpoint lessons learned from model partnerships. Research finds that corporate-humanitarian collaborations, when successfully established, provide their partners with mutual benefits such as knowledge transfer, sharing of resources and best practices. Also, the improvement of a company‟s public image and awareness can be achieved. Humanitarian aid organisations profit from the building of capacity in between disasters, including staff training and the provision of readily accessible resources from the partnering company. The findings also demonstrate that such collaborations are expected to show a moderate development in the future but need to be built on clear partnership agreements determining the scope of involvement as well as each partner‟s goals and objectives. Research is solely based on collaborations between commercial logistics companies and humanitarian aid agencies focusing on relief operations after sudden-onset natural disasters (e.g. earthquakes). Further research is needed especially in the field of risk assessment and risk management of collaborations, the influence of such partnerships on employees‟ overall performance, as well as the development of specific key performance indicators (KPIs). This thesis provides logistics companies and humanitarian relief professionals as well as researchers and readers interested in this particular topic, an overview of the current state of development of cross-sector collaborations. Furthermore, the main critical success factors the logistics industry and the humanitarian aid sector believe are necessary to establish successful partnerships are highlighted.
Keywords: Business logistics; Disaster relief; Emergency management